THE EXISTENCE OF MORTGAGE RIGHTS IN THE BASIC AGRARIAN LAW AND THE DYNAMICS OF ITS REGULATION IN THE MODERN ERA - Richard (Awang Long Law Review, 2026)
The development of land registration systems and electronic transactions has driven the transformation of land administration in Indonesia, including the implementation of Mortgage Rights as a collateral institution for land rights. This study aims to analyze the existence of Mortgage Rights in the Indonesian land law system and examine the dynamics of its regulation in the modern era. This study uses a normative legal research method with a statute approach and a conceptual approach . The legal materials used include primary, secondary, and tertiary legal materials analyzed qualitatively through literature studies. The results of the study indicate that the existence of Mortgage Rights is maintained as the only material collateral institution specifically charged with land rights based on the Basic Agrarian Law and Law Number 4 of 1996 concerning Mortgage Rights. This existence is not only reflected in normative recognition, but also in the continuity of its function in providing legal certainty, legal protection, and supporting the national financing system. The dynamics of Mortgage Rights regulation in the modern era take place through the transformation of the administrative mechanisms for encumbrance, registration, verification, and cancellation of Mortgage Rights into an electronic system without changing the substance of Mortgage Rights as a material security right. These changes indicate that modernization is more directed at the implementation of land administration rather than changes to the legal construction of Mortgage Rights. Therefore, the development of Mortgage Rights regulations needs to be directed at harmonization between Law Number 4 of 1996 and regulations regarding electronic systems and digital land administration in order to accommodate the development of land registration systems and electronic transactions without reducing legal certainty and the effectiveness of Mortgage Rights institutions.